2021
DOI: 10.3389/fphys.2021.771605
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Subjective and Objective Alertness During Exposure to Bright Light in the Afternoon for 5 h

Abstract: Light can induce an alertness response in humans. The effects of exposure to bright light vs. dim light on the levels of alertness during the day, especially in the afternoon, as reported in the literature, are inconsistent. This study employed a multiple measurement strategy to explore the temporal variations in the effects of exposure to bright light vs. regular office light (1,200 lx vs. 200 lx at eye level, 6,500 K) on the alertness of participants for 5 h in the afternoon. In this study, 20 healthy adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Another study reported that the increase in illuminance from 200 lx to 1200 lx for five hours starting at 14:00 elevated physiological markers of alertness. However, it did not enhance either subjective or performative indicators of alertness [50]. Nevertheless, if the physiological markers of alertness do not translate to either subjective or performative indicators then such a scenario would be ineffective for non-visual stimulation in an office setting.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study reported that the increase in illuminance from 200 lx to 1200 lx for five hours starting at 14:00 elevated physiological markers of alertness. However, it did not enhance either subjective or performative indicators of alertness [50]. Nevertheless, if the physiological markers of alertness do not translate to either subjective or performative indicators then such a scenario would be ineffective for non-visual stimulation in an office setting.…”
Section: Discussionmentioning
confidence: 91%
“…Luo et al [50] compared the alerting effect of regular office light (1200 lx vs. 200 lx) for 5 hours in the afternoon and found that in comparison to subjective and performative indicators, the EEG activity may be more responsive to the bright light-induced alertness response during the day.…”
Section: Effect Of the Illuminancementioning
confidence: 99%